Failure and Fatigue Fracture at the Femoral Stem-Metaphyseal Sleeve Junction in a Modular Knee Prosthesis: A Case Report. Issue 3 (July 2018) - Christiner, Tom; Pabbruwe, Moreica B.; Kuster, Markus
Abstract : Case: A 66-year-old active man had undergone revision total knee replacement surgery with a femoral metaphyseal sleeve and a cemented stem in 2013 after loosening of the implant following the primary knee arthroplasty. He was overweight and had a high activity level, and there had been progressive osteolysis surrounding the distal aspect of the femoral sleeve. In 2017, the metaphyseal sleeve had loosened, resulting in corrosion of the threaded taper and catastrophic failure of the implant, with a fracture of the stem at the junction of the sleeve. Conclusion: This unique method of failure in this knee implant highlights a weak point in the design. Clinicians must be aware of the increased likelihood of this type of failure with these implants in patients who have contributory factors.